(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: World Health Organization (WHO) suggests that Exclusive Breast Feeding (EBF) is the best nutrition for infants. Still, globally, breast feeding rates remain lower than required to protect women’s and children’s health. The study aimed to determine the level of knowledge and practices on EBF and complementary feeding among mothers in the rural area of Chattogram District, Bangladesh. Materials and methods: This descriptive cross-sectional study was conducted in two rural private hospital Outpatient Departments in Lohagara, Chattogram, Bangladesh, during the COVID-19 pandemic from July 2021 to December 2021. Two hundred and forty mothers with children of age 6 to 24 months selected by purposive sampling were interviewed using a questionnaire to elicit information on infant breastfeeding practices and their associated factors. Results: One hundred eighty (75%) mothers knew about breastfeeding initiation soon after birth, and 192 (80%) were knowledgeable about EBF for six months, but 69.6% and 65%, respectively, initiated breastfeeding just after birth and practiced EBF. One hundred forty-nine (62.1%) mothers knew the proper age forstarting complementary feeding, but only 135 (56.3%) mothers practiced it. 84 (35%) mothers did early initiation of complementary feeding while 21 (8.8%) mothers delayed it beyond six months. Conclusions: Though the mothers were knowledgeable regarding various aspects of EBF and complementary feeding, there was a practice gap among mothers. JCMCTA 2022 ; 33 (2) : 84-88